2020
DOI: 10.1089/jop.2019.0062
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical 0.01% Atropine for Controlling Near Work-Induced Transient Myopia: A Randomized, Double-Masked, Placebo-Controlled Study

Abstract: Purpose: To investigate the efficacy and safety of topical low-concentration (0.01%) atropine for controlling near work-induced transient myopia (NITM) in a young Chinese population. Methods: This was a randomized, double-blinded, placebo-controlled study. The participants were randomly divided into the 0.5% hydroxypropyl-methylcellulose-treated group (control group) or 0.01% atropine-treated group (study group). Participants' pulse rate, respiration rate, intraocular pressure, pupil diameter, and magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…22 In another study, no serious complications were noted compared with the placebo group after using 0.01% atropine for 14 days in a study of the Chinese population. 23 In accordance with previous studies, no allergy was observed, and our results showed that after 1 month of atropine administration, nine subjects (12.5%) complained of discomfort, mainly soreness and mild tingling, immediately after administration, but this subsided after a few seconds, and 1 subject (1.39%) was dazzled, although these symptoms were mild. However, these symptoms no longer occurred when followed up at 3 and 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…22 In another study, no serious complications were noted compared with the placebo group after using 0.01% atropine for 14 days in a study of the Chinese population. 23 In accordance with previous studies, no allergy was observed, and our results showed that after 1 month of atropine administration, nine subjects (12.5%) complained of discomfort, mainly soreness and mild tingling, immediately after administration, but this subsided after a few seconds, and 1 subject (1.39%) was dazzled, although these symptoms were mild. However, these symptoms no longer occurred when followed up at 3 and 6 months.…”
Section: Discussionsupporting
confidence: 92%
“… 20 , 21 , 22 Recently, a randomized study assessed the efficacy of a low-concentration of atropine (0.01%) on the initial NITM magnitude among Chinese myopic children aged 6–15 years. 23 They reported that the initial NITM magnitude was significantly reduced for approximately 0.45D after 7 and 14 days of instilling atropine. 23 This study suggests, to some extent, that atropine may slow down the myopia progression through reducing initial NITM magnitude.…”
Section: Discussionmentioning
confidence: 99%
“… 23 They reported that the initial NITM magnitude was significantly reduced for approximately 0.45D after 7 and 14 days of instilling atropine. 23 This study suggests, to some extent, that atropine may slow down the myopia progression through reducing initial NITM magnitude. However, there was no direct data on the association between NITM and refractive change, so this remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…15,28 Some studies suggested that topical use of 0.01% atropine can efficiently control transient myopia caused by work in adolescents. 29 However, the study of Larkin et al 30 showed that 0.01% atropine eye drops considerably slows the progression of myopia in a group of American children who have been treated for more than 2 years. In a 6-month prospective study of Cheng et al, 31 atropine at a concentration of 0.01% shows no obvious side effects on the ocular surface in children with myopia.…”
Section: Discussionmentioning
confidence: 99%